Genetic Carrier Screening (GCS) in Clinical Practice: A Current Survey of Physician Impressions and Attitudes [37G]. Issue 1 (May 2017) - Briggs, Allison; Nouri, Parvaneh; Galloway, Michael; Yaklic, Jerome L.; Maxwell, Rose; Lindheim, Steven
Abstract : INTRODUCTION: GCS is an important component of preconception and prenatal care and allows for cost-effective and efficient screening. Given the complexity, we evaluated current physicians' attitudes towards GCS and Expanded (E)-GCS to assess current practice. METHODS: The 32-question survey was distributed to Obstetricians, Gynecologist and Subspecialists through SurveyMonkey by Listserve database and our Premiere Health System. RESULTS: Overall 297 Obstetrician and Gynecologists responded. Compared to 5 years ago, providers were more likely to offer ethnic based GCS or E-GCS prior to conception (24%, vs 13%, P < .001) or post-conception (27%, vs 16%, P < .001). Currently, GCS based on family history (47%) was offered more than E-GCS (17%, P < .001). Ideally, physicians believed GCS should be offered during pre-conception counseling (57%) and during early pregnancy (33%), but limited by current office policy where it was more likely to be discussed during fertility (51%, ) and post-miscarriage (43%) appointments, compared to contraceptive counseling (19%) and annual exams (14%, P < .001). GCS was addressed by physicians (67%) in most practices and 57% stated they were comfortable with counseling, however, only 32.0% were comfortable discussing a positive screening result, (P < .01). Fifty-five percent felt E-GCS should not be offered until clinical significance of each disease was fully understood compared to 26% who felt should be offered regardless. CONCLUSION: GCS is an underutilized resource which may be due to the level of comfort with counseling and beliefs surrounding E-GCS. Continued education and training programs are warranted to implement GCS and E-GCS in routine practice.